Physicochemical properties and microwave absorption performance of Co3O4 and banana peel-derived porous activated carbon composite at X-band frequency - Yusuf, J.Y. (Elsevier Ltd, 2021)
Agricultural waste-derived absorbers have drawn extensive attention in electromagnetic wave absorption owing to their unique advantages such as good carbon content and porosity. In this study, porous activated carbon (PAC) was derived from banana peel via chemical activation and carbonization at different temperatures. Then, Co3O4@PAC composites were prepared using the facile hydrothermal method. The thermal stability, phase crystallinity, chemical composition, surface morphology, and porosity of the samples were studied using TGA, XRD, FTIR, XPS, FESEM, and SAP characterization techniques, respectively. Co3O4@PAC700 composite with a cornales flower-like morphology achieved an optimum reflection loss (RL) of â44.50 dB at 2.0 mm thickness. Likewise, Co3O4@PAC600 showed an optimum RL value of â51.50 dB at 11.39 GHz with a matching thickness of 2.5 mm. The magnetic loss, interfacial polarization, porous flower-like structure, and conduction loss contributes adequately towards the superior absorption performance of Co3O4@PAC composites at X-band frequency. The unique flower-like morphology of the composites with good porosity would favour EM wave scattering and multiple reflections of EM wave, thereby resulting in high attenuation of the EM wave. The flower-like morphology prolongs the electromagnetic wave propagation path which would favour gradual attenuation of the electromagnetic wave. This work suggests that the Co3O4@PAC composites can be considered as a promising absorber for EM absorption application. This study provides a new path to designing novel magnetic and dielectric composite for effective microwave absorption. Â© 2021 Elsevier B.V.